The effectiveness of land use planning in urban housing developments in Selangor / Hamizah Yakob - Yakob, Hamizah (Institute of Graduate Studies, UiTM, 2018)
Land use planning are considered to be some of the contributing factors in achieving better housing development mainly in urban areas. However, the effectiveness of land use planning for housing development is still questionable, leading to issues related to housing shortages, location, housing choices and its quality. The shortcomings in the implementation of land use planning practice for housing development have arguably contributed to these problems. The research sets out to examine the effectiveness of development plans and planning control in terms of its implementation in urban housing development in Selangor. Four objectives outlines which highlights the current housing planning activities in preparing development plans including formulation of policy; determination of land location, land size as well as guidelines; and its implementation through planning control during housing applications and approvals, were analysed based on the perception of respondents. The research is measured through quantitative analysis based on a structured questionnaire survey conducted among government planners and planning consultants. To further explore the issues and problems, expert interviews were conducted with expert town planners. For fourth objective, the strength and weaknesses of planning aspects influencing housing development were analysed using an IPA Matrix which focuses on important items that require high attention for improvement based on its effectiveness. Findings reveal that there are weaknesses in the implementation of development plans within its policy, development strategies and planning control process…